PENINGKATAN MOTIVASI BELAJAR MATEMATIKA MELALUI PEMBELAJARAN MATEMATIKA KONTEKSTUAL - Antika, Rindi (Pusat Penelitian dan Pengembangan Reka Karya Amerta (REKARTA), 2019)
This study focuses on enhancement of student?s learning motivation. This is a quasi experimental research with non equivalent control group design. Sample were taken by purposive sampling technique so that selected 22 experimental group students and 22 control group students from VIIIth grade of junior high school in Bandung, The experimental group was given contextual mathematics learning, while the control group was given regular learning. Questionnaire of motivation were used as research instrument. The results show that enhancement of student?s learning motivation with contextual mathematics learning better than students who received regular learning.